MODERN METHODS OF DIAGNOSTICS OF LICHEN PLANE - Samadova Shakhzoda Isakovna (Western European Studies, 2025)
Recently, scientists around the world have been paying great attention to the problem of diagnosing and treating chronic diseases of the oral mucosa. The main problem for studying the epidemiology of LP is the differences not only in the frequency of patients visiting dentists and dermatologists separately, but also in the analysis of the assessment of the frequency of simultaneous lesions of the oral mucosa and skin, naturally, separately when patients visit dentists and dermatologists
Keywords: Defensins; flowmetry; fluctuations in blood flow